Benefits of dry comminution of biomass pellets in a knife mill. (August 2017) - Williams, Orla; Lester, Edward; Kingman, Sam; Giddings, Donald; Lormor, Stephen; Eastwick, Carol
Abstract : The potential benefits of dry comminution in a knife mill for a diverse range of biomass pellets are explored. The impact of dry comminution on energy consumption, particle size and shape, is examined as well as the link between milling and mechanical durability. Biomass pellet comminution energy was significantly lower (19.3–32.5 kW h t −1 [fresh] and 17.8–23.2 kW h t −1 [dry]) than values reported in literature for non-densified biomass in similar knife mills. The impact of drying was found to vary by feedstock. Dry grinding reduced milling energy by 38% for mixed wood pellets, but only 2% for steam exploded pellets. Particle size and shape, particle distribution dispersion, and distribution shape parameters changes between fresh and dry milling were also material dependent. Von Rittinger analysis showed that to maximise mill throughput, pellets should be composed of particles which can pass through the screen and thus have a neutral size change. A strong correlation was found between pellet durability and energy consumption for fresh biomass pellets. Dry grinding has the potential to significantly reduce energy consumption without compromising the product particle size, as well as enhancing product quality and optimising biomass pellet comminution and combustion. Highlights: Dry milling of woody, herbaceous, fruit and treated biomass pellets in knife mill. Von Rittinger theory used to analyse the fracture behaviour of biomass pellets. Correlation between mechanical durability and mill energy obtained. Dry comminution results in enhanced product quality for reduced mill energy.